The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/ejn.15760
|View full text |Cite
|
Sign up to set email alerts
|

Frequency‐ and phase‐dependent effects of auditory entrainment on attentional blink

Abstract: Attentional blink (AB) is the impaired detection of a second target (T2) after a first target has been identified. In this paper, we investigated the functional roles of alpha and theta oscillations on AB by determining how much preceding rhythmic auditory stimulation affected the performance of AB. Healthy young adults participated in the experiment online. We found that when two targets were embedded in rapid serial visual presentation (RSVP) of distractors at 10 Hz (i.e., alpha frequency), the magnitude of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
(87 reference statements)
0
7
0
Order By: Relevance
“…In line with this notion, unisensory visual entrainment administered at alpha frequencies has been widely demonstrated as effective in entraining endogenous alpha oscillations of the cortical and subcortical visual pathways [28,100,101], with associated functional improvements in visual abilities and visual awareness [38,39,42,43,46,58,99]. Moreover, despite a more limited range of available empirical evidence, converging findings have recently also documented the effectiveness of auditory sensory entrainment in entraining the ongoing neuronal oscillations of the visual system, with consequent functional modulation of visual performance [40,41,47]. Indeed, it has been demonstrated that auditory stimuli are capable of inducing a phase reset of the endogenous neuronal oscillations of the visual system, synchronizing oscillatory activity through the functionally interconnected nodes between sensory systems [48,[66][67][68][69][70][71].…”
Section: Alpha-band Sensory Entrainment: Current State-of-the-art And...mentioning
confidence: 87%
See 3 more Smart Citations
“…In line with this notion, unisensory visual entrainment administered at alpha frequencies has been widely demonstrated as effective in entraining endogenous alpha oscillations of the cortical and subcortical visual pathways [28,100,101], with associated functional improvements in visual abilities and visual awareness [38,39,42,43,46,58,99]. Moreover, despite a more limited range of available empirical evidence, converging findings have recently also documented the effectiveness of auditory sensory entrainment in entraining the ongoing neuronal oscillations of the visual system, with consequent functional modulation of visual performance [40,41,47]. Indeed, it has been demonstrated that auditory stimuli are capable of inducing a phase reset of the endogenous neuronal oscillations of the visual system, synchronizing oscillatory activity through the functionally interconnected nodes between sensory systems [48,[66][67][68][69][70][71].…”
Section: Alpha-band Sensory Entrainment: Current State-of-the-art And...mentioning
confidence: 87%
“…Accordingly, in a subsequent study, Ronconi and colleagues [41] confirmed the efficacy of alpha-band auditory entrainment in reducing the AB magnitude, providing EEG evidence of an association between increased posterior and frontal alpha activity during the rhythmic stream of auditory stimuli and the detection of the visual target. Furthermore, Kawashima and colleagues [47] recently employed an auditory alphaband entrainment (10 Hz) in a web-based modality in order to replicate the findings of Ronconi and colleagues [40,41], increasing the duration of pre-target auditory entrainment (5 s) and showing that auditory rhythmic stimulation worked to increase visual detection performance in an AB task.…”
Section: Alpha-band Auditory Entrainmentmentioning
confidence: 98%
See 2 more Smart Citations
“…Luminance‐related changes directly modulate the feedforward response of V1 (striate cortex) that is independent of psychological factors like attentional load (Bombeke et al, 2016), suggesting that changes in pupil size due to autonomic regulation also affect visual perception to some degree. Note that while blinks are often considered informative of attentional or other arousal states (Demiral et al, 2023; Kawashima et al, 2022; Schwabe et al, 2011), their effect on pupil size is probably rather related to basic visual function.…”
Section: Methodsmentioning
confidence: 99%